2000
DOI: 10.1111/j.1365-2141.2000.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of human herpesvirus 6 DNA in peripheral blood leucocytes are correlated to platelet engraftment and disease in allogeneic stem cell transplant patients

Abstract: Summary. The aim of this study was to correlate human herpesvirus (HHV)-6 viral load with clinical symptoms in allogeneic stem cell transplant (SCT) patients. Seventy-four patients were monitored during the first 3 months after SCT using a qualitative polymerase chain reaction (PCR) for HHV-6 DNA. HHV-6 was detected in 181 out of 494 samples (36%) from 58 (78%) patients. These 181 samples were analysed using a quantitative competitive PCR. DNA could be quantified from 146 out of 181 samples (80´6%). The HHV-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 28 publications
7
128
2
Order By: Relevance
“…In our study, along with others, we have already reported the main consequence of HHV6 infection was to delay neutrophil and plt recoveries, especially in early reactivating patients. 25,27,37 Delayed engraftment is a well-known complication of cord blood transplant occurring at a higher incidence when compared with other source of SCs. [1][2][3][4]6 The role of HHV6 in delayed engraftment raises logically the question of HHV6 prophylaxis in CB transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, along with others, we have already reported the main consequence of HHV6 infection was to delay neutrophil and plt recoveries, especially in early reactivating patients. 25,27,37 Delayed engraftment is a well-known complication of cord blood transplant occurring at a higher incidence when compared with other source of SCs. [1][2][3][4]6 The role of HHV6 in delayed engraftment raises logically the question of HHV6 prophylaxis in CB transplant.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 HHV-6 encephalitis develops concomitant to peak blood HHV-6 DNA. 3,5,7,8 Some studies in which blood levels of HHV-6 DNA have been monitored have shown a correlation between HHV-6 reactivation and the development of HHV-6 encephalitis, 1,[3][4][5][6][7][8]56 but others have failed to demonstrate such associations. 2,57,58 The reasons for these divergent results may be because of the low incidence of HHV-6 encephalitis even in patients with HHV-6 reactivation.…”
Section: Hhv-6 Reactivation and Hhv-6 Encephalitis: We Know Hhv-6 Reamentioning
confidence: 99%
“…[1][2][3][4][5][6] The duration of displaying positive HHV-6 DNA in plasma is only 1-2 weeks in most cases. 3,5,7,8 HHV-6B accounts for most reactivation events.…”
Section: Hhv-6 Reactivation and Hhv-6 Encephalitis: We Know Hhv-6 Reamentioning
confidence: 99%
See 1 more Smart Citation
“…Among 338 recipients of bone marrow transplant, the incidence of central nervous system (CNS) symptoms associated with HHV-6 in the cerebrospinal fluid (CSF) was only 1.5% (five patients). 4 Recipients grafted with stem cells from HLA-mismatched donors have an increased risk of HHV-6 reactivation and disease, 4,5 which is also implicated as a cause of the initiation and exacerbation of graft-versus-host disease (GVHD). Here, we describe a patient who developed life-threatening acute GVHD following HHV-6 encephalitis after allogeneic peripheral blood stem cell transplantation (PBSCT) from an HLA-haploidentical sibling mismatched for noninherited maternal HLA antigens (NIMA).…”
mentioning
confidence: 99%